2017
DOI: 10.18632/oncotarget.16507
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt1s in donor cells is a barrier to SCNT-mediated DNA methylation reprogramming in pigs

Abstract: Low development of somatic cell nuclear transfer embryos could be due to the incomplete DNA methylation reprogramming, and Dnmt1s existing in donor cells may be one cause of this disrupted DNA methylation reprogramming. However, the reprogramming pattern of Dnmt1s and its effect on DNA methylation reprogramming in cloned embryos remain poorly understood. Here, we displayed that along with the significantly higher Dnmt1 expression at the zygotic gene activation stage of cloned embryos, genomic methylation level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The abnormal expression of DNMTs in donor cells results in DNA methylation defects and aberrant embryo development in pigs [33]. Piccolo et al reported that TET1 and TET2 respectively mediate the demethylation of imprinted genes and pluripotent genes, respectively, during reprogramming [34].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of DNMTs in donor cells results in DNA methylation defects and aberrant embryo development in pigs [33]. Piccolo et al reported that TET1 and TET2 respectively mediate the demethylation of imprinted genes and pluripotent genes, respectively, during reprogramming [34].…”
Section: Discussionmentioning
confidence: 99%
“…These modifications are added and removed by specific enzymes, whose abundance can influence development. For example, removing DNMT1 from pig donor cells facilitated genome methylation and promoted cloned embryo production between zygotic gene activation and the blastocyst stage (Song et al, ). Alternatively, the efficiency of SCNT embryo production was improved by augmenting the level of H3K9Ac in pig donor cells—either by increasing chromatin access (Nebendahl et al, ) or by reducing the level of H3K9me3 (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…reprogramming, leading to a developmental stop in SCNT embryos (Song et al, 2017). Moreover, its removal allows for an efficient activation of genes essential for embryonic development, thus increasing SCNT efficiency (Song et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in achieving efficient methylation reprogramming in SCNT embryos may be a consequence of the resistance of tissue-specific epigenetic patterns to be reprogrammed by the oocyte (Sepulveda-Rincon et al, 2016). Studies have reported that embryo development can be improved by reducing DNMT expression using epigenetic modifier agents and siRNA technology (Song et al, 2017). It has also been found that SCNT embryo development can be significantly improved by strategies that stimulate changes in DNA methylation and histone modifications, such as the use of 5-Aza-2-deoxycytidine (ZdC) (Christman, 2002;Patra and Bettuzzi, 2009;Tsuji et al, 2009), procaine (para-aminobenzoyl-diethylamino-ethanol) (Villar-Garea et al, 2003;Li et al, 2018), S-adenosyl-l-homocysteine (SAH) ( Jeon et al, 2008;Zhang et al, 2014), and scriptaid (Zhang et al, 2014), during cell culture.…”
Section: Introductionmentioning
confidence: 99%